Digital Promotion Strategies to Improve Customer Satisfaction in the Indonesian Film Industry: A Case Study of the Film Rumah Teteh - Indriasari, Retno; Rudianto, Rudianto; Hadiningrat, Suharyono S.; Sompi, Pingkan Luciawati; Pakpahan, Marisi (CV Putra Publisher, 2026)
The rapid development of digital technology has significantly transformed media consumption patterns in Indonesia, including the way audiences discover and engage with films. Social media, creative digital content, and influencer marketing have become essential components of promotional strategies in the film industry, as they enable production companies to build emotional engagement with audiences. In this context, film producers are required to design effective digital promotion strategies to attract viewers and enhance customer satisfaction. This study aims to analyze the implementation of digital promotion strategies carried out by PT Ruang Visual in promoting the film Rumah Teteh, and to examine the role of social media marketing activities and influencer marketing in shaping audience perceptions and customer satisfaction within the Indonesian film industry.This research employs a qualitative approach using an autoethnographic method, involving eight informants consisting of producers, content creators, audiences, and other stakeholders within the film promotion ecosystem. The findings reveal that digital promotion strategies utilizing platforms such as TikTok, Instagram, and Facebook effectively increase audience awareness and generate early enthusiasm toward the film. In addition, collaboration with credible influencers strengthens audience trust and creates positive perceptions about the film. The study also finds that audience satisfaction is strongly influenced by the consistency between promotional messages and the actual viewing experience, as explained by Expectation–Disconfirmation Theory. Overall, integrated digital promotion strategies can enhance audience engagement and customer satisfaction in the film industry